2018
DOI: 10.1152/ajprenal.00528.2017
|View full text |Cite
|
Sign up to set email alerts
|

Klotho and activin A in kidney injury: plasma Klotho is maintained in unilateral obstruction despite no upregulation of Klotho biosynthesis in the contralateral kidney

Abstract: In a new paradigm of etiology related to chronic kidney disease-mineral and bone disorder (CKD-MBD), kidney injury may cause induction of factors in the injured kidney that are released into the circulation and thereby initiate and maintain renal fibrosis and CKD-MBD. Klotho is believed to ameliorate renal fibrosis and CKD-MBD, while activin A might have detrimental effects. The unilateral ureter obstruction (UUO) model is used here to examine this concept by investigating early changes related to renal fibros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 71 publications
5
34
1
Order By: Relevance
“…Although Wnt signalling have been implied in the regeneration of injured of kidney tissue, persistent activation and dysregulation of the Wnt pathways underlie fibrosis and progressive renal failure [ 28 ]. In agreement with previously reported results from our group, UUO was associated with induction of expression of genes related to fibrosis [ 27 ]. ICG-001 abolished the induced expression of pro-fibrotic genes in the UUO experiment, confirming the bioavailability and effect of the compound, in agreement with previous results by Hao et al [ 19 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although Wnt signalling have been implied in the regeneration of injured of kidney tissue, persistent activation and dysregulation of the Wnt pathways underlie fibrosis and progressive renal failure [ 28 ]. In agreement with previously reported results from our group, UUO was associated with induction of expression of genes related to fibrosis [ 27 ]. ICG-001 abolished the induced expression of pro-fibrotic genes in the UUO experiment, confirming the bioavailability and effect of the compound, in agreement with previous results by Hao et al [ 19 ].…”
Section: Discussionsupporting
confidence: 93%
“…Renal fibrosis is the final common pathway of all progressive renal diseases [ 23 ]. Several studies and previous results from our group have shown that kidney injury could reactivate developmental programs involved in nephrogenesis, attempting renal repair [ 24 27 ]. Wnt family members and factors controlling Wnt function are critical morphogens in the developing kidney [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A mouse model of CKD revealed upregulation of activin expression in the skeleton, vasculature, heart, and kidneys 23 . In addition, a ligand trap for the activin type IIA receptor exhibited beneficial effects in murine CKD models, alleviating vascular disease and renal fibrosis 35 , renal osteodystrophy 36 and nephrogenic anemia 37 . These previous findings implied a causative role of activin A in the pathogenesis of CKD and its potential role as a target of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental studies, elevated activin A was derived directly from renal tubule epithelial cells in streptozotocin-treated38 and UUO25 rat models, from myofibroblasts in Alport CKD mice,22 25 renal interstitial cells in Ldlr –/– high fat-fed mice with ablative CKD,22 infiltrating macrophages in lupus nephritis mice23 and glomerular culture supernatants in an anti-Thy1 glomerulonephritis rat model 39. Furthermore, while UUO induced activin A gene expression in the kidney and its release into the circulation, these findings were not observed in the plasma, contralateral kidney or remnant kidney of unilaterally nephrectomized rats having similar fall in total GFR, suggesting the obstructed kidney as the source 24. In our human diabetes studies, albuminuria, reflective of kidney injury, directly correlated with activin A in plasma and urine.…”
Section: Discussionmentioning
confidence: 96%
“…However, activin A becomes abundantly expressed in the injured kidney in experimental models of acute kidney injury (AKI),19 20 glomerulonephritis and CKD 21–23. Circulating activin A levels doubled in unilateral ureter obstruction (UUO) rats while levels remained unchanged in unilateral nephrectomized controls with similar kidney function, suggesting the obstructed kidney as the source 24. Renal tubular cells release activin A, which acts as a paracrine factor that promotes fibroblast proliferation, contributing to kidney fibrosis and CKD progression 17 19 25.…”
Section: Introductionmentioning
confidence: 99%